Salmonella enterica serovar agona for anti-tumor therapy - Cheah, Yoke Kqueen; Khoo, Chai Hoon; Taraq Naem Zia, Ubaidah Naim (2013)
The present invention provides Salmonella enterica serovar Agona and/or knockdown strain of Salmonella enterica serovar Agona, optionally genetically engineered, for use in anti-tumor therapy.